An Early Neolithic enclosure at the site of Vlaho, Pelagonia. (April 2023) - Naumov, Goce; Przybyła, Marcin; Gibaja, Juan F.; Penezić, Kristina; Antolín, Ferran; Sabanov, Amalia; Fidanoska, Aneta
Abstract: Abstract : Recent study of Vlaho in Pelagonia confirms that it is the earliest known Neolithic settlement in North Macedonia. Multidisciplinary research of the architecture and material reveals a complex enclosure site dating to the seventh millennium BC, with dozens of ditches, daub buildings, white painted pottery and domesticated plants and animals.